2021
DOI: 10.3892/etm.2021.10256
|View full text |Cite
|
Sign up to set email alerts
|

miR‑133a‑3p regulates the proliferation and apoptosis of intestinal epithelial cells by modulating the expression of TAGLN2

Abstract: Sepsis is one of the most common diseases in patients in intensive care units. Intestinal barrier dysfunction serves a critical role in the pathogenesis and progression of sepsis. Therefore, preservation of the intestinal epithelial barrier function is an area of ongoing research in the treatment of sepsis. The present study investigated the effects of miR-133a-3p on the proliferation and apoptosis of intestinal epithelial cells and the possible mechanism underlying its actions. miR-133a-3p was used to upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This study found that H. meleagridis was involved in cecal in ammation at different stages by inducing differential expression of different miRNA in the host. For example, some DEMs, including miR-29b-3p, miR-449a, miR-146a-5p, miR-31-5p, miR-128-3p, miR-133a-3p, miR-204, let-7b, has been proved to be related to the intestinal mucosal integrity [35], intestinal in ammatory response [36]. Among these, miR-29b-3p, miR-449a, let-7b were only differential expressions at 10 DPI or 15 DPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that H. meleagridis was involved in cecal in ammation at different stages by inducing differential expression of different miRNA in the host. For example, some DEMs, including miR-29b-3p, miR-449a, miR-146a-5p, miR-31-5p, miR-128-3p, miR-133a-3p, miR-204, let-7b, has been proved to be related to the intestinal mucosal integrity [35], intestinal in ammatory response [36]. Among these, miR-29b-3p, miR-449a, let-7b were only differential expressions at 10 DPI or 15 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…Gga-miR-133a-3p was down-regulated expression in intestinal of chicken's coccidiosis [39] and was up-regulated expression in cecal of chicken's Salmonellosis [40]. Moreover, down-regulated gga-miR-133a-3p may protect the intestinal barrier by promoting the proliferation of intestinal epithelial cells and inhibiting apoptosis [35]. Up-regulated miR-146a-5p inhibited the expression of CLIC4 and NLRP3 in ammasome downstream in ammatory factors and reduced intestinal in ammatory reaction and injury in mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…And the other 59 DEMs showed the similar expression patterns at the two time points, indicating that these miRNAs were involved in the regulation of persistent infection of H. meleagridis . In addition, the numerous DEM homologs, including miR-29b-3p, miR-449a, let-7b, miR-146a-5p, miR-204, miR-128-3p, and miR-31-5p, miR-133a-3p, obtained from the chicken cecum in this study, has been shown to be associated with the intestinal mucosal integrity [ 36 ], intestinal inflammatory response [ 37 – 42 ], suggesting that these DEMs or DEM homologs may play the important roles in the cecum response against H. meleagridis . For instance, miR-133a-3p showed a downregulated expression in the cecum tissue of chickens following H. meleagridis infection at both time points, which was consistent with that in intestine of chicken coccidiosis [ 43 ], but showed an opposite expression pattern in cecum of chicken Salmonellosis [ 44 ] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-133a-3p showed a downregulated expression in the cecum tissue of chickens following H. meleagridis infection at both time points, which was consistent with that in intestine of chicken coccidiosis [ 43 ], but showed an opposite expression pattern in cecum of chicken Salmonellosis [ 44 ] . A previous study found that miR-133a-3p inhibited the proliferation and promoted the apoptosis of intestinal epithelial cells by limiting the expression of TAGLN2 [ 36 ]. This indicates that miR-133a-3p might have a central role in chickens resistance to pathogenic, and could be responsible for the persistent inflammatory response and intestinal mucosal integrity in host cecum throughout the infection process.…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening of research in recent years, researchers have discovered that the dysfunction of the intestinal mucosal barrier leads to the imbalance of intestinal microbiota; the entry of endotoxins into the blood through the barrier may induce the release of large amounts of inflammatory factors and thus accelerate the development of sepsis ( 11 ). In addition, intestinal epithelial and endothelial cells are further disrupted when sepsis-induced excessive inflammatory responses occur, further exacerbating intestinal permeability and intestinal flora imbalance and thus inducing a vicious cycle of sepsis ( 12 ). Moreover, these interactions lead to the activation of large numbers of genes, inflammatory cytokines (e.g., the proinflammatory cytokines TNF-α andIL-6 and the anti-inflammatory cytokine IL-4), and chemokines that are released by macrophages under the mediation of downstream signaling molecules involved in inflammatory responses ( 13 ).…”
Section: Introductionmentioning
confidence: 99%